T\The answer would be 3 6/10, or 3.6.
Answer:
3(x - 12)(x + 2)
Step-by-step explanation:
Given
3x² - 30x - 72 ← factor out 3 from each term
= 3(x² - 10x - 24) ← factor the quadratic
Consider the factors of the constant term (- 24) which sum to give the coefficient of the x- term (- 10)
The factors are - 12 and + 2 , since
- 12 × 2 = - 24 and - 12 + 2 = - 10 , thus
x² - 10x - 24 = (x - 12)(x + 2) and
3x² - 30x - 72 = 3(x - 12)(x + 2)
34.5=4h+7c
(34.5-7c)/4=h
Put h= (34.5-7c)/4 into another equation
30.5=8h+3c
30.5=2(34.5-7c)+3c
30.5=69-14c+3c
11c=38.5
c=38.5/11
Put c=38.5/11 into one of the equations
to calculate the h.